Transformative Learning in Early Childhood Parenting in the Family Environment - Edi Widianto (Jurnal Pendidikan Humaniora, 2014)
Transformative Learning Pengasuhan Anak Usia Dini di Lingkungan KeluargaAbstract: The purpose of this research are: (1) a general description of transformative learning in early childhood parenting, (2) the problems faced by parents in early childhood parenting, (3) actions in addressing the problem of parental nurturing early childhood through transformative learning, (4) the impact of transformative learning in early childhood parenting. The study used a qualitative approach with a case study design. Research sites were in the Village District of Wates Duwet Kediri. The informants are parents who have children aged 0-6 years. The process of data collection using in-depth interviews, focus groups, participant observation, and documentation. Analysis using the interactive analysis according to Miles & Huberman models. The results of the study are: (1) parental many transformative learning experience in caring for his children; (2) the problems faced by parents in early childhood parenting a child manages a unique character, habituation child, independence training, discipline, and responsibility for the child, the child’s social interaction, self-confident child training, sex education early childhood; (3) the actions of parents in resolving parenting issues early age in the form of awards, advice, warnings, penalties, acquiescence to the child; (4) a transformative impact on parents internally and externally.Key Words: transformative learning, parenting, early childhood, family Abstrak: Tujuan penelitian ini untuk menjelaskan: (1) gambaran umum transformative learning pada pengasuhan anak usia dini, (2) masalah-masalah yang dihadapi orangtua dalam mengasuh anak usia dini, (3) tindakan-tindakan yang dilakukan orangtua dalam mengatasi masalah pengasuhan anak usia dini melalui transformative learning, (4) dampak transformative learning dalam pengasuhan anak usia dini. Penelitian menggunakan pendekatan kualitatif dengan rancangan studi kasus. Lokasi penelitian di Desa Duwet Kecamatan Wates Kabupaten Kediri. Informan penelitian adalah orangtua yang mempunyai anak usia 0-6 tahun. Proses pengumpulan data menggunakan wawancara mendalam, FGD, observasi partisipatif, dan dokumentasi. Teknik analisis data menggunakan interactive analysis models menurut Miles & Huberman. Hasil penelitian adalah: (1) orangtua banyak mengalami pembela-jaran transformatif dalam mengasuh anak-anaknya; (2) masalah-masalah yang dihadapi orangtua dalam mengasuh anak usia dini berupa mengelola karakter yang unik anak, pembiasaan anak, melatih kemandirian, disiplin, dan tanggung jawab anak, interaksi sosial anak, melatih percaya diri anak, pendidikan seks anak usia dini; (3) tindakan orangtua dalam menyelesaikan masalah pengasuhan anak usia dini berupa pemberian penghargaan, nasihat, peringatan, hukuman, pembiaran kepada anak; (4) dampak transformatif pada orangtua secara internal dan eksternal.Kata kunci: transformative learning, pengasuhan, anak usia dini, keluarga